The Emerging Threat of Extractives Sector to Intact Forest Landscapes - Grantham, Hedley S.; Tibaldeschi, Paolo; Izquierdo, Pablo; Mo, Karen; Patterson, David J.; Rainey, Hugo; Watson, J. E. M.; Jones, Kendall R. (Frontiers in Forests and Global Change, 2021)
As demand for commodities increases globally, resource-rich countries are focal areas for industrial expansion. The extractives sector is driving unprecedented growth of infrastructure (e.g., roads, railways and pipelines) into sparsely populated regions, which contain some of the world’s remaining intact forests. Yet, the extent of the threat posed by an increased footprint of extractive industries is not well understood. Here we provide a novel global assessment of the potential threat posed to tropical Intact Forest Landscapes (IFLs), continuous patches of forest that have no remotely sensed signs of human activity or forest fragmentation, from the extractives sector including mining, oil and gas projects, using one of the most extensive global spatial datasets on extractives concessions to date. We found ∼20% of the global tropical IFL estate is designated as extractive’s concessions, presenting an enormous threat to these forests. Oil and gas concessions overlap with 408,000 km2 of tropical IFLs (7.85% of total IFL area), with the biggest overlap in the Democratic Republic of the Congo and Papua New Guinea. Mining concessions overlap with 589,000 km2 (11.33%) of tropical IFL area, mainly in Brazil and Democratic Republic of Congo. As the majority of concessions overlapping IFLs are currently at the exploration stages for all types of extractives, now is the time to plan for reducing the potential threat through strategies such as identifying “no go” areas and applying the mitigation hierarchy. Nations and investors should undertake regional strategic environmental assessments to reduce impacts, including potential indirect and cumulative impacts of multiple projects and other threats in the landscape. We also call for banks that funders of extractives projects to apply global best practice industry environmental safeguards that recognize the value of intact forests and the risk of cumulative impacts to these unique sites.